2011
DOI: 10.1021/ed1006053
|View full text |Cite
|
Sign up to set email alerts
|

GC–MS Quantitation and Identification of Bisphenol-A Isolated from Water

Abstract: b S Supporting Information O ne of the biggest challenges in trace organic analysis is concentrating any given sample enough to reliably identify and quantitate above the method detection limit. There are several ways to do this depending on the sample matrix. For aqueous samples, liquidÀliquid extraction can be used to partition an analyte to the organic solvent layer. Another example is solid-phase extraction (SPE) where the aqueous layer is passed through a solid phase to selectively extract the analyte of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…This is probably due to benzylic carbocation, resulting in the loss of methyl group from BPA. The resulting ion with m/z 213 was very stable resulting in it being the base peak in the mass spectrum [ 28 ]. Munguia–Lopez et al reported m/z 213 as the main ion with further fragments including m/z 228 (molecular ion), 110, and 91 [ 115 ].…”
Section: Recent Advancements In Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to benzylic carbocation, resulting in the loss of methyl group from BPA. The resulting ion with m/z 213 was very stable resulting in it being the base peak in the mass spectrum [ 28 ]. Munguia–Lopez et al reported m/z 213 as the main ion with further fragments including m/z 228 (molecular ion), 110, and 91 [ 115 ].…”
Section: Recent Advancements In Analytical Methodsmentioning
confidence: 99%
“…For example, Denmark, France, Sweden, and Belgium have restricted the use of BPA in food packaging for young children. Denmark imposed a ban on the use of BPA for the manufacturing of plastic materials in contact with food intended for children aged 0–3 years [ 28 ]. In 2012, France adopted a law of suspending all BPA containing materials coming into contact with foods intended for children of 0–3 years of age from January 2013, and all other food contact materials from January 2015 [ 29 ].…”
Section: Regulatory Aspectsmentioning
confidence: 99%
“…Their high polarities require prior derivatization before the GC/MS analysis, so as to reduce their polarity and enhance their volatility. As a commonly used derivative agent for phenols or alcohols, BSTFA 28 was selected as the derivative agent for their derivatization in the current study.…”
Section: Optimization Of the Derivatization Conditionsmentioning
confidence: 99%
“…A variety of analytical approaches have been used to detect BPA, such as gas chromatography-mass spectrometry (GC-MS), [5] fluorometry, [6] enzyme-linked immunosorbent assay, [7] liquid chromatography-mass spectrometry (LC-MS), [8] high performance liquid chromatography (HPLC), [9] high performance liquid chromatography coupled to UV, [10] molecular imprinting technique, [11] electrochemical method. [12] Although these methods are accurate and sensitive, their application is often limited due to the complexity of the operation and the high cost of the instrument.…”
Section: Introductionmentioning
confidence: 99%